Responding to health and social needs of aging Latinos in new-growth communities: a qualitative study - Kim Larson; Holly F. Mathews; Essie Torres; C. Suzanne Lea (BMC, 2017)
Abstract Background The development of new-growth communities of Latino immigrants in southern states has challenged the traditional health and social service infrastructure. An interprofessional team of service providers, Latino leaders, and university faculty partnered to establish linkages with the Latino community and providers serving aging adults and to explore the health and social needs of aging Latinos residing in a rural region. Methods A qualitative descriptive study was conducted through a community-university partnership, the Aging Latino Research Team (ALRT). Data were generated from nine focus groups and 15 key informant interviews with Latino and non-Latino community members and service providers in rural, eastern North Carolina (ENC). Results Thematic analysis was used to identify common patterns and form recommendations for future research and programs. Themes common to Latino participants were: "We are put off to one side"; "If I can't work, I can't survive"; and "Without documents, you are no one." Themes common to non-Latino participants were: "Older Latinos are not well served"; "Older Latinos are invisible"; "Older Latinos are undocumented and afraid"; and "Older Latinos are wandering the highway". Conclusion A major finding of this research was the extent to which discrepancies in perceptions between Latino participants and non-Latino participants exist. These discrepancies revealed ethnic stereotyping and cultural insensitivity as major barriers in access to care.